2018
DOI: 10.1080/02688697.2018.1426726
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical thrombectomy – is time still brain? The DAWN of a new era

Abstract: The advancement of endovascular treatment for stroke has led to improved morbidity and mortality for patients. Future challenges include delivering these treatments to stroke centers worldwide.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 64 publications
1
11
0
Order By: Relevance
“…31 Seners et al indicated that the likelihood of early neurologic deterioration is correlated with more proximal and longer clot lengths, potentially allowing selection for EVT of those patients more like to Figure 1 The NNT for major RCTs of mechanical thrombectomy and other key medical therapies. 5 (A) Illustrating the NNT for seven RCTs. (B) The NNT for key medical therapies including decompressive haemicraniectomy for MCA infarction, defibrillation for cardiac arrest, thrombectomy for AIS (the DAWN Trial), goal-directed therapy for acute sepsis, thrombolysis for AIS <3 hours, ipratropium and beta-agonist nebulizer for childhood asthma, thrombolysis for AIS >3 hours and <4.5 hours, PCI for highrisk ST-elevation myocardial infarction, aspirin for ST-elevation myocardial infarction, antibiotics for the primary prevention of rheumatic fever and bariatric surgery on mortality in obese patients.…”
Section: Mild Strokesmentioning
confidence: 99%
“…31 Seners et al indicated that the likelihood of early neurologic deterioration is correlated with more proximal and longer clot lengths, potentially allowing selection for EVT of those patients more like to Figure 1 The NNT for major RCTs of mechanical thrombectomy and other key medical therapies. 5 (A) Illustrating the NNT for seven RCTs. (B) The NNT for key medical therapies including decompressive haemicraniectomy for MCA infarction, defibrillation for cardiac arrest, thrombectomy for AIS (the DAWN Trial), goal-directed therapy for acute sepsis, thrombolysis for AIS <3 hours, ipratropium and beta-agonist nebulizer for childhood asthma, thrombolysis for AIS >3 hours and <4.5 hours, PCI for highrisk ST-elevation myocardial infarction, aspirin for ST-elevation myocardial infarction, antibiotics for the primary prevention of rheumatic fever and bariatric surgery on mortality in obese patients.…”
Section: Mild Strokesmentioning
confidence: 99%
“…Recently published trials have demonstrated the safety and efficacy of endovascular treatment up to 6 h after the onset of IS [9][10][11][12][13][14]. In addition, a new generation of randomized controlled clinical trials with specific selection criteria based on patient characteristics has made it possible to extend the time window in which it is possible to treat patients with IS due to occlusion of proximal anterior circulation vessels with thrombectomy (16-24 h) [15][16][17][18]. However, due to the restricted eligibility criteria [19] for patients to receive these treatments, many stroke patients do not receive active therapies.…”
Section: Introductionmentioning
confidence: 99%
“…We calculated an overall NNT of 3.6, which indicates superiority over other treatments and procedures (e.g., intravenous thrombolysis performed within 3 hours from symptom onset produced an NNT of 8). 10 In light of these findings, the therapeutic window for endovascular procedures could be extended up to 24 hours. However, our pooled analysis revealed that the main benefits resulted in the last two trials that applied stricter inclusion and exclusion criteria.…”
Section: Discussionmentioning
confidence: 99%